Optical and thermoelectric properties of nano-particles based Bi2(Te1−xSex)3 thin films. (January 2017) - Adam, A.M.; Lilov, E.; Petkov, P.
Abstract: Nano-particles of Bi2 Te3 and Bi2 (Te1−x Sex )3 films were deposited using vacuum thermal evaporation technique from previously prepared bulk alloys synthesized by melting method. Optical and thermoelectric properties were studied in the temperature range of 300–473K. The formation of none- and Se-doped Bi2 Te3 nano-particles was verified by EDX and XRD analysis. TEM, SEM and AFM analysis showed the prepared films are polycrystalline in nature. The measurements of electrical conductivity and Seebeck coefficient, alongside with thermal conductivity calculations, resulted in the highest values of thermoelectric power at high temperature to be reported. The maximum value of power factor was calculated at 62.82917 μWK −2 cm −1 for (Bi2 Se0.3 Te1.7 ) sample at 463 K. On the addition of Se to Bi2 Te3 film, a significant decrease of the electronic thermal conductivity (Kel ) from 2.181 × 10 −2 to 0.598 × 10 −2 (μW/cm.K) could be achieved. Figure of merit (ZT) calculations showed a maximum value of 0.85 at room temperature, for Bi2 Te3 . Besides the increase of ZT value for all samples at higher temperature, surprisingly, a value of 2.75 for (Bi2 Se1.2 Te1.8 ) was obtained. We believe our results could open avenues for new applications.